Phenotypic characterization of Streptococcus sanguis virulence factors associated with bacterial endocarditis. - Herzberg, M C (1990)
Certain strains of Streptococcus sanguis adhere (Adh+) selectively to human platelets and, in plasma, induce them to aggregate (Agg+) into in vitro thrombi. In this study, we examined 18 recent endocarditis and dental plaque isolates of microorganisms that were biotyped as S. sanguis for coexpression of platelet interactivity phenotypes with another possible virulence factor in bacterial endocarditis, dextran synthesis. Detectable production of extracellular glucosyltransferase ranged from 0.2 to 66 mU/mg of culture fluid for 10 representative strains tested. Production of extracellular or cell-associated glucosyltransferase, fructosyltransferase, and soluble or insoluble dextrans was not necessarily coexpressed with platelet interactivity phenotypes, since the levels of production of soluble and insoluble dextrans varied among representative Adh+ Agg+ and Adh- Agg- strains. Analysis of a second panel of 38 fresh dental plaque isolates showed that S. sanguis distributes in a reproducible manner into the possible phenotype groups. Strains with different platelet interactivity phenotypes were distinguished with a panel of four murine monoclonal antibodies (MAbs) raised against Adh+ Agg+ strain 133-79 and screened to rule out artifactual reactions with antigenic components in culture media. The MAbs reacted selectively with Adh+ Agg+ strains in a direct-binding, whole-cell, enzyme-linked immunosorbent assay and also inhibited their interactions with platelets. Analysis of minimal tryptic digests of many strains, including variants that failed to bind the MAbs, suggested that some noninteractivity phenotypes possess cryptic surface determinants. Since the ability to adhere to platelets and induce them to aggregate is relatively stable, these traits may be useful in a phenotyping scheme for these Lancefield nontypeable streptococci.